Improving nurse competence in health centers through practice-based training - Lumastari Ajeng Wijayanti; Hijrah Hijrah; Rida Millati; M. Khalid Fredy Saputra; Suprapto Suprapto; Yoga Tri Wijayanti (Edukasi Ilmiah Indonesia, 2025)
Health services in Puskesmas have a strategic role in improving the quality of public health. However, the competence of nurses in health centers often still needs improvement, especially in terms of technical skills, communication, and patient-based services. This Community Service (PkM) activity aims to improve the competence of nurses at the Health Center through practice-based training and mentoring. The implementation method involves stages: needs analysis, competency-based training, case simulation, and direct mentoring in the workplace. This activity is carried out collaboratively using a participatory approach, where nurses are actively involved in each stage to ensure the relevance and sustainability of learning. The results showed a significant improvement in the concept understanding and practical ability of nurses, which was reflected in the increase in skill evaluation scores before and after training. Mentoring also helps nurses in applying the knowledge gained into the context of daily work. In conclusion, practice-based training and mentoring is an effective strategy to improve the competence of nurses in health centers, which can ultimately contribute to improving the quality of public health services. This program is recommended to be implemented more widely with continuous support from related parties.